IMPLEMENTASI UPAH MINIMUM KOTA PEKANBARU TAHUN 2013 - Riza Agustine; Zaili Rusli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Pekanbaru City government has set a minimum wage for Rp.1.450.000 Pekanbaru City, - per month for the year 2013, as stated in Riau Governor Regulation No. 67 Year 2012 on Minimum Wage District / City Seprovinsi Riau in 2013. With the enactment of the Governor of Riau expected labor welfare will increase and as an effort to improve the welfare of society. The problem in this research is how the implementation of the minimum wage Pekanbaru City and inhibiting factors in carrying out the implementation of the minimum wage of Pekanbaru. As for the goal in this study to determine the extent of implementation of the minimum wage Pekanbaru City and to determine the factors inhibiting the implementation of the minimum wage in the process of Pekanbaru.Theoretical concept that researchers used is implementation, public policy. This study uses qualitative research methods to study descriptively. In collecting the data, the researcher used interview techniques, observation, and literature study. By using key informants as a source of information.The results showed that the implementation of the minimum wage Pekanbaru City conducted by the Department of Labor has not been effective Pekanbaru City. Limiting factors in implementing the minimum wage implementation of Pekanbaru, namely: lack of complaints that workers can not wage minimum wage, maximum less supervision, the absence of strict sanctions.Keywords: Implementation, Public Policy, minimum wage.